الديمقراطية والليبرالية والعلمانية في الفكر الغربى - الشمري، نادية جاسم كاظم علي (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2016)
The Study explained that Democracy is part of the Psychology of the individual and his life Which became the basis of which Freedom the base equality individual suffered from the domination of the Church and feudalism and the looting of rights Political, Social , Cultural rights and Freedoms and the system of authoritariam rule who narrowly on human rights freedoms robbed of the their life in the past was not a constitution that guarantees the right life, Search consists of an introduction and three search and a conclusion and supplements. Realized Western Democracy Through the Views and ideas of Philosophers and Political and economic theorists, and Writers Who have fought Political , Social and Economic Realities that have been experienced by the peoples and regions of the liberal world of denial of rights and inequality, which opposed pioneers demanding investigation Human Freedoms . That freedom represents Liberal nucleus the latter foundation upon which the secular Which represents religious freedom is the nucleus of the liberal.
Keywords: الدراسات الإنسانية -- التاريخ الحديث -- الديمقراطية -- الليبرالية -- العلمانية -- الديمقراطية الليبرالية